Cloud Technology in Business - Ashish Kamat; Suren Hembram; Nitin Vaishnav; Varsha Sontakke (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The focus of the entire globe is on online data storage, where data is accessible at any time via a network. This concept is called as Cloud Computing. Many firms have chosen the flexibility and benefits of cloud computing over the traditional technique of local software hosting and storage. In recent years, the value of cloud-based public services surged in billions. Its expansion is exacerbated by the overuse of social media, e-commerce, and mobiles. This study focuses on the significance of implementing Cloud Technology in business organisations [micro, Small Medium Companies [SMBs], and Small Medium Businesses [SMEs] and by what means it influences development in business, based on a review of the relevant research literature.